A Nurse Shadowing Program for Physicians: Bridging the Gap in Understanding Nursing Roles. (June 2020) - Johnson, Courtney M.; Khan, Amir; Stark, Sarah; Samee, Mohammed
Abstract : OBJECTIVE: A physician-nurse shadow program was established to improve interdisciplinary collaboration. BACKGROUND: Ineffective communication between physicians and nurses leads to poor outcomes in patient satisfaction, safety, and associate engagement. Physician unfamiliarity of the nursing process is identified as a root cause. METHODS: First-year resident physicians shadowed nurses for a 4-hour shift. Residents did not function as a physician during the shadowing experience but participated in nursing workflow and tasks. Participants completed a Likert-scale rating and qualitative survey before and after the shift. RESULTS: The survey measured confidence in communication and perception of workflow. Confidence levels increased in all areas by 29% for residents and 34% for nurses. Data demonstrated improved physician understanding of nursing workflow and inspired recommendations to enhance communication. CONCLUSIONS: First-year resident physicians practiced direct communication skills and experienced hands-on nursing care during the shadow program. The initiative provided an environment for mutual learning and interdisciplinary relationship-building. Abstract : Supplemental digital content is available in the text.